15z-2=(2z+3)

Simple and best practice solution for 15z-2=(2z+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15z-2=(2z+3) equation:


Simplifying
15z + -2 = (2z + 3)

Reorder the terms:
-2 + 15z = (2z + 3)

Reorder the terms:
-2 + 15z = (3 + 2z)

Remove parenthesis around (3 + 2z)
-2 + 15z = 3 + 2z

Solving
-2 + 15z = 3 + 2z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-2z' to each side of the equation.
-2 + 15z + -2z = 3 + 2z + -2z

Combine like terms: 15z + -2z = 13z
-2 + 13z = 3 + 2z + -2z

Combine like terms: 2z + -2z = 0
-2 + 13z = 3 + 0
-2 + 13z = 3

Add '2' to each side of the equation.
-2 + 2 + 13z = 3 + 2

Combine like terms: -2 + 2 = 0
0 + 13z = 3 + 2
13z = 3 + 2

Combine like terms: 3 + 2 = 5
13z = 5

Divide each side by '13'.
z = 0.3846153846

Simplifying
z = 0.3846153846

See similar equations:

| 3x-(12x-x)=5+2(x-1)-1 | | 3y+5y+2y= | | 6r-6=72-6 | | 5n-30=20 | | 3x-(12-x)=5+2(x+1)-1 | | 5y=11x-7 | | 3(x+5)-2=6x-3(-4+x) | | -8x+3=25 | | 5y=11x+7 | | LNx=-1.6 | | Log(8x-7)/log(x) | | -6f+13=-9z+24 | | 9(5+x)=8(x-4) | | 5+2X=14-4N | | 4y-13=43 | | -8b/5=-1 | | 4x-38=9x-3 | | 5x+39=154 | | 6+65x=52x+18 | | x-5x^(1/2)-6=0 | | 2.6(x-0.8)=9 | | 7(y+6)=3+6y | | 6+65x=52+18 | | x^2+21x+30=9x+3 | | 112x+6=5x | | t/4-6=9 | | x/6-2/7=6 | | 5(b-4)=6(3+b) | | 2sin^2x=1-sinx | | |x/3-4|0 | | x^2-2x-14=10 | | (15x-4x)-(10-x)= |

Equations solver categories